The Influence of Mind Mapping Technique on Students’ Writing Skills at MA Guppi Samata - ,, Nurhalima; Mardiana, Mardiana; Ahmad, Djuwairiah (Universitas islam Negeri Alauddin Makassar, 2023)
This research aims to find out the influence of the Mind Mapping Technique on students’ writing skills at MA Guppi Samata. Since writing in English seems to be one of the most difficult tasks to do. The researcher intended to help the students write a descriptive text by applying the mind mapping technique. The researcher performed the quasi experimental research method to find the influence of the technique. The population of this research was 49 first-grade students at MA Guppi Samata. The subjects of this study were 25 students from the experimental class and 24 students from the control class. The researcher did the treatment by teaching descriptive text and applying the mind mapping technique. The data were collected through the test. The result of the data was analyzed quantitatively. By comparing the value of the t-test and t-table to analyze the hypothesis, the researcher defined the result of the research. The researcher found that there was a significant difference between students’ scores in the post-test for the experimental class and the controlled class. The mean score of post-tests (7.44) in the experimental class was greater than the mean score of post-tests (6.54) in the controlled class. Furthermore, the comparison of the t-test (3.333) and the t-table (2.021) indicated that the t-test was higher than the t-table at the level of significance (α) = 0.05 with a degree of freedom (df) = (N1 + N2)-2 = (25 + 24) – 2 = 47. Based on the t-test and t-table comparison results, it was shown that the mind-mapping technique influenced the students’ writing skills. It has been proved that mind mapping is one of the techniques that helps students find and organize ideas for writing, especially descriptive text. Students are facilitated by the diagram in mind mapping that represents the way of organizing ideas linked to the central keyword with branches containing related words.